2022
DOI: 10.1136/gutjnl-2021-325013
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 signaling drives chronic ER stress responses to promote NAFLD progression

Abstract: ObjectivesNon-alcoholic fatty liver disease (NAFLD) can persist in the stage of simple hepatic steatosis or progress to steatohepatitis (NASH) with an increased risk for cirrhosis and cancer. We examined the mechanisms controlling the progression to severe NASH in order to develop future treatment strategies for this disease.DesignNFATc1 activation and regulation was examined in livers from patients with NAFLD, cultured and primary hepatocytes and in transgenic mice with differential hepatocyte-specific expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…45,57--59 Inflammatory cells could trigger several signals including inflammatory molecules, lipid messengers, ROS and endoplasmic reticulum stress, which perturbs hepatocytes and causes metabolic abnormality, which promotes NAFLD progression. 47,60,61 Works also demonstrate that NETs could promote HCC progression by inducing inflammatory microenvironments. 45,62 In this study, we found that GCN5L1 triggered ferroptosis and released HMGB1, which increased the infiltration of neutrophils and promoted the formation of NETs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,57--59 Inflammatory cells could trigger several signals including inflammatory molecules, lipid messengers, ROS and endoplasmic reticulum stress, which perturbs hepatocytes and causes metabolic abnormality, which promotes NAFLD progression. 47,60,61 Works also demonstrate that NETs could promote HCC progression by inducing inflammatory microenvironments. 45,62 In this study, we found that GCN5L1 triggered ferroptosis and released HMGB1, which increased the infiltration of neutrophils and promoted the formation of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have demonstrated that NETs promote inflammation, which might recruit multiple immune cells 45,57 . ‐ 59 Inflammatory cells could trigger several signals including inflammatory molecules, lipid messengers, ROS and endoplasmic reticulum stress, which perturbs hepatocytes and causes metabolic abnormality, which promotes NAFLD progression 47,60,61 . Works also demonstrate that NETs could promote HCC progression by inducing inflammatory microenvironments 45,62 .…”
Section: Discussionmentioning
confidence: 99%
“…TUDCA can treat cholestatic diseases mainly by increasing the bile flow and BA secretion, attributed to choleretic and cytoprotective effects on hepatocytes ( Paumgartner and Beuers, 2002 ), and its mechanism is mainly related to alleviating ERS ( Latif et al, 2022 ). However, in this study, the level of TUDCA was found to be elevated in NASH mice.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of IF and IHC images was performed either using ImageJ Fiji 62 (by manually counting positive cells, measuring the fluorescence intensity of the entire field of view, or using semi-automatic macros as described previously 63 ), or using QuPath 64 v0.4.3. In QuPath, cell detection was performed using the built-in detection feature, obtaining intensity measurements per cell, per nucleus or per cytoplasm, which were used for positive cell quantification using single measurement classifications (or compound classifiers for double-positive cells).…”
Section: Methodsmentioning
confidence: 99%